Hubungan Kadar Hemoglobin dan Gangguan Fungsi Ginjal Pada Diabetes Melitus Tipe 2 di RSUD Menggala Tahun 2021 - Putri, Vivit Millani; Nofita, Nofita; Primadiamanti, Annisa (Jurnal Ilmiah Wahana Pendidikan, 2025)
Today, there are many genetic diseases that cause chronic complications. The 2018 Riskesdas report states that there was an increase in prevalence in DM patients by 2.0% in 2013 and to 3.4% in 2018 of the total number of DM patients in Indonesia (Riskesdas, 2018). The purpose of this study was to see the relationship between hemoglobin levels and impaired kidney function in type 2 diabetes mellitus at Menggala Hospital in 2021. This study used recorded data obtained from Menggala Hospital. The results of this study indicate that CKD patients with a history of Type 2 DM at the Menggala Hospital with the most gender characteristics are women as many as 63 people (56.8 %). The most age is 51-55 as many as 48 people (43.6%). The highest duration of illness characteristic was 5 years as many as 25 people (22.7%). Then it can be concluded that the relationship between Hb levels, GFR, and frequency of hemodialysis with patient characteristics all have a significant relationship / there is a relationship, except for the relationship between hemodialysis frequency and gender characteristics